PENGARUH ROA, ROE, EPS DAN NPM TERHADAP PERUBAHAN HARGA SAHAM PERUSAHAAN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2022 - Salman Rasyid; Munawar (Journal of Development Economic and Social Studies, 2024)
Before engaging in stock market transactions, investors evaluate companies that release their shares on the Stock Exchange. This evaluation covers several factors, such as the company's ability to generate profits, the level of returns, and risks. Investors participate in the stock market with the expectation of receiving rewards or income from their investments. For those who invest in company stocks, the goal is to obtain income in the form of dividends or capital gains. This research aims to determine the influence of Return On Asset, Return On Equity, Earnings Per Share, and Net Profit Margin on changes in stock prices in construction companies listed on the Indonesia Stock Exchange. The population used in this study consists of 12 construction companies that have been continuously listed for 7 consecutive years during the period 2016-2022 on the Indonesia Stock Exchange. The data used are secondary data obtained through purposive sampling. The data analysis method in this research involves hypotheses. The results of this study show that Return On Asset and Return On Equity have a partially negative and insignificant effect on changes in the stock prices of construction companies listed on the Indonesia Stock Exchange. Meanwhile, Earnings Per Share and Net Profit Margin have a partially positive and significant effect on changes in the stock prices of construction companies listed on the Indonesia Stock Exchange.